(3QSGdI aj eYQaI GdfZeGJs
(3ChdgG (B:s
(3Chd eGjLH GdGYJfGA Hg eYQaI GdfZeGJ GdKeGf GdJi YdjgG eOGQ GdZfGA hGdCdMGf cdgG s
(3BNQgG (B:s
(3hbO hVYhG GdCUhd GdWHhY haQYgG eKdC Ydi UhQJi TLQg jXgQ HPdc cd CUd , heGjJaQY efg CMjGfkG , UhQg Pdc ceG JQi Ef TGA Gddg s
(3fTQ GdCSJGP gfQi LhQL aGQeQ gPg GdQSGdI eY ebOeI hedGMXGJ hJQLeI Edi GddZI GdGfLdjRjI ai eLdI GdLeYjg Gdedcjg GdCSjhjI ai GdYOOjf GdUGOQjf ai TgQ GHQGjd (B1931 (3hjfGjQ (B1932s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B57 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3afhf LejdI (B498) s
Keywords: (3GdehSjbi hGdZfGAs